Respons Pertumbuhan Tanaman Nilam (Pogostemon cablin Benth.) Terhadap Variasi Ketersedian Air Sebagai Strategi Adaptasi Terhadap Perubahan Iklim - Lapanjang, Iskandar M.; Syafrizal, Yusril (LPPM Universitas Mataram, 2025)
atchouli (Pogostemon cablin Benth.) is an aromatic plant, well known to produce valuable essential oils. Patchouli productivity in Indonesia from 2014 to 2020 was quite fluctuated. Plant growth and productivity is influenced by climate factors and water availability. Drought for instance can disrupt photosynthetic cycle and lowering the biomass production. Patchouli plants have shallow roots, susceptible more to drought stress. This experiment was conducted to identify the effect of watering field capactiy status on growth and biomass production of Patchouli. The experiment was carried out at the Greenhouse for Research and Assessment of Agricultural Technology (IP2TP) Sidondo, Sidondo III Village, Sigi Biromaru District, Sigi Regency, Central Sulawesi, from January to March 2022. This study used Randomized Block Design (RAK) which consisted of one factor, namely diferent water levels expressed in percentage of water field capacity (KL). There were 6 differents KL treatment K0 = 100%, K1 = 90%, K2 = 80%, K3 = 70%, K4 = 60%, K5 = 50%. Each treatment was repeated 4 times with 3 plants, in total there were 72 experimental units (polybags). The results showed that 90% and 100% of water field capacity (KL) increase the growth and impact to higher patchouli biomass, 46.35 g and 47.93 g, respectively. When KL is dropped to 80%, the biomass is reduced 20%. It is therefor, to maintain higher biomass production, the water field capacity shall be kept at least 90%.